PERAN UKM KONVEKSI DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI PEREMPUAN DI KABUPATEN PAMEKASAN - Nurul Alfian; Runik Puji Rahayu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The existence of the convection UKM in Pamekasan Regency participates to contribute to the improvement of the economic welfare of women, especially convection employees, the majority of whom are female. This study aims to determine how the contribution of convection UKM in improving women's economic welfare and to describe the inhibiting and supporting factors of convection UKM in increasing women's economic welfare.This type of research uses a descriptive method with a qualitative approach. The results of this study indicate that the increase in the economic welfare of women is marked by an increase in income, the convection business contributes in the form of additional income for women who initially do not have their own income. Researchers found that there are other factors beyond earning this income, namely the husband's income and also the condition of the community itself.